A novel imprinted sensor based on Ag-modified composite MOFs for selective detection of Rhodamine B in river. Issue 5 (October 2022) - Li, Hongji; Li, Dongze; Wang, Junfu; Yu, Haochen; Huang, Chengsi; Jiang, Wei; Liu, Chunbo; Che, Guangbo; Wang, Dandan
Abstract: In this work, a novel imprinted sensor based on Ag-modified composite metal organic Frameworks (MOFs) was synthesized for selective detection to Rhodamine B (RhB) in river. UIO-66(NH2 ) was firstly dispersed on the surface of ZIF-8 with the assistance of PVP, and Ag nanoparticles were dispersed on the surface by in-situ reduction. The ZIF-8/UIO-66(NH2 )/Ag-MIPs (AZU-MIPs) were synthesized by the process of precipitation polymerization. It was proved from the analysis results that AZU-MIPs presented sensitive and selective detection property to RhB. Furthermore, AZU-MIPs also presented stability and repeatability property during the practical samples detection. There was an obvious linear relationship between concentration and Raman intensity when the concentration of RhB changed between 10 −6 M and 5 × 10 −11 M. The detection of limit (LOD) was 5 × 10 −11 M, and the correlation coefficient (R 2 ) was 0.9984. It could be considered that the novel imprinted sensor presented a promising candidate for Rhodamine B and other organic fluorescent dye detection in the river, and this work also provided an application prospect to the monitor of water environment. Graphical Abstract: UIO-66(NH2 ) was synthesized by the solvothermal process under ultrasonic and the ZIF-8 was dispersed on the surface of UIO-66(NH2 ) by the assistance of PVP. The composite MOFs were applied as support materials to increase the adsorption capacity by the plenty of open-framework structure. Then the Ag NPs were dispersed on the surface of ZIF-8/UIO-66(NH2 ) by the in-situ reduction. Finally, the ZUA-MIPs were synthesized by the procedure of precipitation polymerization. The ZUA-MIPs would obtain the specific recognition cavities when the templates were removed from the MIPs. These materials presented selective property to the template molecules and could be applied into the practical samples detection. This investigation could broaden the SERS detection field and provide a new procedure to the organic pollutants detection. ga1 Highlights: Supply more active sites for attachment of Ag nanoparticles to increase the sensitivity. Combination of two MOFs to increase the adsorption capacity. Improving the selective detection property by the process of imprinted polymerization.